Soil temperature, soil water content and electric conductivity monitoring from Disko Island for thermal-hydrological investigations - Zastruzny, Sebastian; Elberling, Bo; Jensen, Karsten Høgh; Sjöberg, Ylva; Liu, Yijing (In: Zastruzny, S et al. (2024): Observed data and simulations results from Disko Island for thermal-hydrological investigations [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.967138, 2024)
The parameters soil temperature, soil water content and electric conductivity are collected at 14 locations along the slope with Decagon Devices 5TE sensors for the time period from August 2015 until August 2021 and are subsequently used to validate the simulations. Additionally validated simulations using the SnowModel (Liston & Elder, 2006) of snow depth measurements of the field site for the years 2014 until 2020 are used to validate the model.
Keywords: Greenland climate; hydrological connectivity; model simulation; Permafrost